Do Incubation Temperatures Affect the Preferred Body Temperatures of Hatchling Velvet Geckos? - Abayarathna, Theja; Webb, Jonathan K. (Frontiers in Ecology and Evolution, 2021)
In many lizards, a mother’s choice of nest site can influence the thermal and hydric regimes experienced by developing embryos, which in turn can influence key traits putatively linked to fitness, such as body size, learning ability, and locomotor performance. Future increases in nest temperatures predicted under climate warming could potentially influence hatchling traits in many reptiles. In this study, we investigated whether future nest temperatures affected the thermal preferences of hatchling velvet geckos, Amalosia lesueurii. We incubated eggs under two fluctuating temperature treatments; the warm treatment mimicked temperatures of currently used communal nests (mean = 24.3 °C, range 18.4–31.1 °C), while the hot treatment (mean = 28.9 °C, range 19.1–38.1 °C) mimicked potential temperatures likely to occur during hot summers. We placed hatchlings inside a thermal gradient and measured their preferred body temperatures (Tbs) after they had access to food, and after they had fasted for five days. We found that hatchling feeding status significantly affected their preferred Tbs. Hatchlings maintained higher Tbs after feeding (mean = 30.6 °C, interquartile range = 29.6 – 32.0 °C) than when they had fasted for 5 d (mean = 25.8 °C, interquartile range =24.7 – 26.9 °C). Surprisingly, we found that incubation temperatures did not influence the thermal preferences of hatchling velvet geckos. Hence, predicting how future changes in nest temperatures will affect reptiles will require a better understanding of how incubation and post-hatchling environments shape hatchling phenotypes.